Peculiar Clinical Presentation of Coxsackievirus B4 Infection: Neonatal Restrictive Cardiomyopathy - Le Van Quyen, Pauline; Desprez, Philippe; Livolsi, Angelo; Lindner, Véronique; Fafi-Kremer, Samira; Helms, Pauline; Antal, Maria Cristina (American Journal of Perinatology Reports, 2017)
Introduction Restrictive cardiomyopathy in fetuses and neonates is extremely rare and has a poor outcome. Its etiology in neonates is elusive: metabolic diseases (e.g., Gaucher, Hurler syndrome), neuromuscular disorders (e.g., muscular dystrophies, myofibrillar myopathies), or rare presentation of genetic syndromes (e.g., Coffin–Lowry syndrome) account for a minority of the cases, the majority remaining idiopathic.Case Study We report the case of a 17-day-old male infant presenting cardiogenic shock following a restrictive dysfunction of the left ventricle. Postmortem investigations revealed coxsackievirus B4 myocarditis with histological lesions limited to the left heart. However, polymerase chain reaction (PCR) for coxsackievirus B4 was positive in the left as well as in the right ventricular samples.Conclusion In conclusion, coxsackievirus myocarditis is a cause of restrictive cardiomyopathy, and its diagnosis should involve PCR screening as a more sensitive technique.
Keywords: restrictive cardiomyopathy; neonate; coxsackievirus B4; PCR